Sustainable feed processing methods to enhance growth and 2 digestibility in freshwater aquaculture: A review - Ariffin, Hidir; Mohd Amran, Aaqillah-Amr; Khairul Adha, A. Rahim; Mohamad Nor, Azra; Honyu, Ma; Rossita, Shapawi; Noordiyana, Mat Noordin; Mhd, Ikhwanuddin (Elsevier B.V., 2026)
Freshwater fish farming is one of the fastest-growing food sectors, contributing significantly to global food security. Despite the impressive global growth of aquaculture, high operational costs remain a major challenge, with feed production costs constituting the highest proportion of expenses. To reduce reliance on expensive materials, alternative ingredients have been explored, but issues such as reduced digestibility may arise. To address these challenges, various processing methods have been developed, ranging from traditional to advanced technologies. This review provides comprehensive insights into these methods, their applications, and their impact on growth performance and nutrient digestibility, with a focus on freshwater fish. Evidence from previous studies shows that alternative ingredients derived from poultry by-products, fisheries by-products, plants, and insects have been processed using techniques such as thermal treatment, extraction, bioconversion, nanoparticles, and pulsed electric fields. These approaches have shown positive effects in improving the growth and digestion of fish. Among these, fermentation methods stand out for their multiple benefits such as converting low-value ingredients into high-value protein sources, providing pre-digested nutrients, additional digestive enzymes, and probiotics. They have a lower environmental impact, use less energy, produce minimal pollution, and are cost-effective. Processing methods continue to evolve to ensure high product output, improved nutrient retention and functionality. Selecting processes that minimize energy use, reduce environmental impact, and lower costs while enhancing ingredient functionality is essential for achieving sustainability in aquaculture.